Substance Use Among Lawyers and Law Students: A Scoping Review - Kizito Aidam; Emefa A. Adawudu (European Journal of Mental Health, 2024)
Introduction: Lawyers are uniquely vulnerable to substance use and disorders due to the use of different substances mainly because of the demanding and adversarial nature of the legal profession. Substance use often begins during law school years.